2012
DOI: 10.1111/j.1365-2672.2012.05246.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deamination increases the survival under acidic conditions in Escherichia coli

Abstract: Aims:  Resistance to acidic stress contributes to bacterial persistence in the host and is thought to promote their passage through the human gastric barrier. The aim of this study was to examine whether nucleosides have a role in the survival under acidic conditions in Escherichia coli. Methods and Results:  We found that adenosine has a function to survive against extremely acidic stress. The deletion of add encoding adenosine deaminase that converts adenosine into inosine and NH3 attenuated the survival in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 33 publications
(60 reference statements)
0
26
0
Order By: Relevance
“…Our group reported that adenosine deamination increased survival under extremely acidic conditions, in addition to amino acid decarboxylation [10]. Furthermore, our group implied that ATP is required for survival under acidic conditions and that one of the ATP-dependent systems is a DNA repair system in E. coli [11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our group reported that adenosine deamination increased survival under extremely acidic conditions, in addition to amino acid decarboxylation [10]. Furthermore, our group implied that ATP is required for survival under acidic conditions and that one of the ATP-dependent systems is a DNA repair system in E. coli [11].…”
Section: Discussionmentioning
confidence: 85%
“…The other two systems are arginine-dependent (AR3) [5], [6] and lysine-dependent (AR4) [7][9] systems. Recently an adenosine-dependent AR system was reported in E. coli , and this system was less active than AR2 but more potent than AR4 [10]. These systems were proposed to regulate the intracellular pH (pHi) at a higher level than the pH of the surroundings [1], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Trace metal mixture (1000×) contained 50 mM FeCl 3 , 20 mM CaCl 2 , 10 mM MnCl 2 and ZnSO 4 , and 2 mM CoCl 2 , CuCl 2 , NiCl 2 , Na 2 MoO 4 , Na 2 SeO 3 , and H 3 BO 3 [31]. Mutants were grown at 37°C in EG medium, which is minimal E medium containing 0.4% glucose [32, 33]. …”
Section: Methodsmentioning
confidence: 99%
“…When a metabolic pathway declines at acidic pH, it would be beneficial for an alternative pathway to work to compensate the decline. It is well known that bacteria have metabolic pathways that function under acidic conditions [7]. These previous insights led us to consider that mammals also have alternative systems working in acidic diseased areas, such as cancer nests, inflammation loci, and areas of infarction.…”
Section: Metabolic Pathways Working Under Acidic Conditionsmentioning
confidence: 99%